Facelift Surgery after Permanent Filler: Outcomes after Removal of Permanent Filler under Local Anesthesia - Ahmad A. F. Alaslawi, MD; Ahmed M. Zeina, MD; Tarek Zahra, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. Permanent fillers were previously used to fix wrinkles associated with aging as they were considered a reasonable choice for facial rejuvenation. However, the subsequent removal of permanent fillers is of great concern to surgeons before performing a facelift surgery. Many studies have evaluated the outcomes of facelift surgery; however, we sought to evaluate the outcomes of facelift surgery which required removal of fillers beforehand. Methods:. This retrospective cohort study evaluated the outcomes of 50 patients with regard to patient satisfaction and postoperative complications of facelift surgery with removal of permanent filler under local anesthesia. A short scar rhytidectomy with superficial muscular aponeurotic system plication was performed. Preoperative and postoperative photographs were analyzed by two independent surgeons to report asymmetry scores ranging from one to three (one none, two slight, and three obvious asymmetries). Patient satisfaction scores were also recorded. Results:. The preoperative presentations of the permanent filler were asymmetry (82%) and disfiguring facial edema (26%). Removing fillers under local anesthesia is generally tolerable, with 56% of patients tolerating rhytidectomy. The degree of the participants’ satisfaction after follow-up was satisfactory; two-thirds of patients (62%) were satisfied. There was a significant difference between surgeons’ preoperative and postoperative assessment of asymmetry scores (P < 0.05). Conclusions:. Permanent filler removal with concomitant face-neck lift surgery has satisfactory outcomes. The procedure length was primarily determined by the patient’s skin characteristics and the severity of the local condition.